Leaving it on the table? An examination of unrealized bargaining power in multimarket buyer–supplier exchanges. Issue 3 (29th September 2020) - Cheng, Li; Craighead, Christopher W.; Crook, T. Russell; Eckerd, Stephanie
Abstract: The study of bargaining power and its role in negotiations has a long history in operations management research. Much of this research has involved buyer–supplier exchanges and has often hinged on the assumption that powerful firms negotiate to wield (fully) their power for favorable outcomes. Yet, it is unclear to what extent firms transform their potential power into realized power. Building on insights grounded in resource dependence theory and literature on competitive dynamics and organization design, we theorize that structural factors (i.e., decentralization, spheres of influence, and mutual dependence) constrain firms from fully realizing their potential power. In doing so, we center on a more nuanced context—multimarket buyer–supplier exchanges, wherein buyers and suppliers handle multiple exchanges across different product markets. We use two controlled negotiation experiments to test our hypotheses. Our results show that in multimarket exchanges, three key factors (and how they sometimes interact) constrain power use. These results offer boundary conditions to extant theory. Most profoundly, our results reveal that centralization (traditionally viewed as a structural lever to enhance power use) alone does not affect power use but has distinct effects conditional on other factors—countering theory and challenging best practices in industry.